Investigation of the potential effects of estrogen receptor modulators on immune checkpoint molecules - Abramenko, Nikita; Vellieux, Fréderic; Veselá, Kateřina; Kejík, Zdeněk; Hajduch, Jan; Masařík, Michal; Babula, Petr; Hoskovec, David; Pacák, Karel; Martásek, Pavel; Smetana, Karel; Jakubek, Milan (Scientific reports, 2024)
Immune checkpoints regulate the immune system response. Recent studies suggest that flavonoids, known as phytoestrogens, may inhibit the PD-1/PD-L1 axis. We explored the potential of estrogens and 17 Selective Estrogen Receptor Modulators (SERMs) as inhibiting ligands for immune checkpoint proteins (CTLA-4, PD-L1, PD-1, and CD80). Our docking studies revealed strong binding energy values for quinestrol, quercetin, and bazedoxifene, indicating their potential to inhibit PD-1 and CTLA-4. Quercetin and bazedoxifene, known to modulate EGFR and IL-6R alongside estrogen receptors, can influence the immune checkpoint functionality. We discuss the impact of SERMs on PD-1 and CTLA-4, suggesting that these SERMs could have therapeutic effects through immune checkpoint inhibition. This study highlights the potential of SERMs as inhibitory ligands for immune checkpoint proteins, emphasizing the importance of considering PD-1 and CTLA-4 inhibition when evaluating SERMs as therapeutic agents. Our findings open new avenues for cancer immunotherapy by exploring the interaction between various SERMs and immune checkpoint pathways.
Keywords: CTLA-4 Antigen; Humans; Estrogen Receptor Modulators; Selective Estrogen Receptor Modulators; selektivní modulátory estrogenních receptorů; antigeny CD279; quercetin; Immune Checkpoint Proteins; lidé; Immunotherapy; modulátory estrogenních receptorů; B7-H1 Antigen; proteiny kontrolních bodů imunitní reakce; Neoplasms; nádory; antigen CTLA-4; antigeny CD274; Programmed Cell Death 1 Receptor; imunoterapie; Quercetin